KETANGGUHAN (HARDINESS) PADA MAHASISWA WIRAUSAHA - Haq, Bella Arini; Akbar, Azza Afirul (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Hardiness is defined as a character that influences an individual's mindset towards the stress faced and determines an effective attitude, while Entrepreneurship is a desirable behavior and is designed to increase economic efficiency, create innovation, create new jobs, and improve the quality of work. The purpose of this study is to determine the hardiness of entrepreneurial students. The method used in this research is a qualitative case study with data collection through interviews. The research subjects are undergraduate students who have run businesses. The results of the study show that entrepreneurial students are able to use coping strategies to carry out their roles as students and also entrepreneurs with all of their backgrounds so hardiness in students is formed since they are able to survive and adapt to everything that is tought or unpleasant. In addition, hardiness can be a foundation of confrontation with the stress experienced. The belief to always be diligent in running a business also have an impact on their desire that it can be beneficial for other people.